Analisis Penyebab Terjadinya Digital Addiction pada Remaja Ditinjau dari Teori Media Entertainment - Mochammad Kresna Noer (Universitas Multimedia Nusantara, 2016)
According to Peter Vorderer’s Theory of Media Entertainment, one of people’s motivations to consume entertainment media is to escape from daily problems and routines, or known also as escapism. For example, when people are feeling bored, they can distract their mind to reduce the stress level by playing game, watching television, and listening to music. According to the theory, people expect to experience enjoyment when consuming entertainment. Escapism motivation expects enjoyment experience to happen at the time of playing game and afterward. Beside of assessing the influence of escapism motivation in consuming experience, this research aims to reveal people’s expectation right after consuming the entertainment media. This study is based on the assumption that people have different feeling when and after consuming the media. After media consumption, people might feeling sorry for not using the time wisely, feeling tired and getting more bored. Keywords: interactive media, digital addiction, communication theory